2022
DOI: 10.1007/s10461-022-03821-3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Effects of an Urban Gardens and Peer Nutritional Counseling Intervention on HIV Treatment Adherence and Detectable Viral Load Among People with HIV and Food Insecurity: Evidence from a Pilot Cluster Randomized Controlled Trial in the Dominican Republic

Abstract: A pilot cluster randomized controlled trial involving two HIV clinics in the Dominican Republic assessed preliminary efficacy of an urban garden and peer nutritional counseling intervention. A total of 115 participants (52 intervention, 63 control) with moderate or severe food insecurity and sub-optimal antiretroviral therapy (ART) adherence and/or detectable viral load were assessed at baseline, 6- and 12-months. Longitudinal multivariate regression analysis controlling for socio-demographics and accounting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The impact of the programme on coping with HIV-related stress and marginalisation through socialisation and community was notable in the narratives of participants, which is of importance considering the high levels of stigma and marginalisation experienced by PLHIV in the DR and globally (41,5456) . Participants also rated the programme’s urban gardens as helpful in the management of HIV, particularly in keeping their clinic appointments and taking medications as prescribed, confirming findings from the overall evaluation, where standard measures of HIV care retention and ART adherence improved (28) . Participants also found the nutritional counselling component and the cooking workshop to be helpful for having a healthier diet, particularly as far as reducing consumption of unhealthy foods, increasing fruit and vegetable intake, and cooking healthy meals.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The impact of the programme on coping with HIV-related stress and marginalisation through socialisation and community was notable in the narratives of participants, which is of importance considering the high levels of stigma and marginalisation experienced by PLHIV in the DR and globally (41,5456) . Participants also rated the programme’s urban gardens as helpful in the management of HIV, particularly in keeping their clinic appointments and taking medications as prescribed, confirming findings from the overall evaluation, where standard measures of HIV care retention and ART adherence improved (28) . Participants also found the nutritional counselling component and the cooking workshop to be helpful for having a healthier diet, particularly as far as reducing consumption of unhealthy foods, increasing fruit and vegetable intake, and cooking healthy meals.…”
Section: Discussionmentioning
confidence: 54%
“…This mixed method process evaluation demonstrates that an integrated peer nutritional counselling and urban gardens programme with PLHIV experiencing food insecurity in the DR was both feasible and acceptable. This is encouraging, given that the intervention trial found preliminary efficacy of improving important HIV clinical outcomes, which, to our knowledge, represents a first for an intervention that integrated peer nutritional counselling in tandem with food generating activities with PLHIV (28) . Our process evaluation also identifies several implementation challenges that should be addressed to improve the benefits and reach of future iterations of the programme.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We excluded studies that explored nutritional counselling and education as part of a package of interventions such that it was not possible to isolate the effect of nutritional counselling/education alone [18]. For the same reason, we also excluded studies where nutritional counselling and education were considered with no appropriate comparator, such as in cases where all study participants received nutritional counselling [19], unless it was possible to consider the study as a pre‐post intervention study.…”
Section: Methodsmentioning
confidence: 99%
“…We found no trials that examined the effect of nutrition counselling on viral load outcomes. One trial examined the effect of nutrition counselling as part of a complex intervention along with urban gardening and cooking workshops [18].…”
Section: Viral Loadmentioning
confidence: 99%